Study of Morality And Human Rights On Former Corruption Prisoners Who Become A Prospective Regional Head - Sulistyani Eka Lestari (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
After the Constitutional Court's Decision No. 56/PUU-XVII/2019 which provides a legal loophole for former corruption convicts to become candidates for Regional Head, there is a polemic in its application and the integrity of the law itself, distancing the function of law as a tool that can be used as a deterrent effect for a crime. The dialectic between the political rights guaranteed by the Constitution which is firmly held by ex-convicts is very contrary to the teachings of morality taught by Immanuel Kant. The study of morality always prioritizes behavior based on inner truth, not because of external factors or in this case while the law allows, which makes humans far from the inner truth itself. This study uses a normative juridical law research with a legal approach and a conceptual approach. The results of this study indicate that the Constitutional Court's decision places the law above morality, by setting aside something that must be owned by the Regional Head, namely a balance between attitudes and behavior. Furthermore, according to the concept of democracy, the state actually has the right to totally limit the political rights of former convicts of corruption not to go forward again or to abolish them completely, in order to guarantee the integrity of the Government from corrupt actors in the future and also to make the law a function of deterrent effect and the last remedy in enforcement, but in fact the state does not implement it, the state prefers to give access to ex-corruption convicts to advance to become candidates for regional heads on the legal basis of this decision.